Reflections of the student teacher. Issue 1 (2nd January 2017) - Meierdirk, Charlotte
Abstract: This paper explores the concept of reflection and its changing role in the journey of the student teacher. It presents part of the findings of a year-long investigation into the reflective practice of student teachers during their training year. Specifically, it investigates the reflections of the student teachers' lessons during the PGCE (Post/Professional Graduate Certificate of Education) year at a higher education institution (HEI) in England. The strengths and weaknesses of the student teachers' lessons are analysed and how these reflections change as they reach Newly Qualified Teachers (NQT) status.